Tumor-reactive T helper cells in the context of vaccination against glioma - Zhao, Binghao; Kilian, Michael; Bunse, Theresa; Platten, Michael; Bunse, Lukas (Cancer cell, 2023)
With the advances in immunogenomics, the majority of tumor-specific antigens were found to be recognized by T helper cells (THCs). This observation led to the development of long epitope vaccines in various cancers. Mechanistically, we are still gaining a deeper understanding of the mode of action of THCs as precision antitumor agonists. Here, we discuss the specific cellular mechanisms of THC functions in glioma immunology and contextualize current advances in anti-glioma vaccination exploiting THCs.